Wear behavior of modified surface layer produced by TIG melting of preplaced Ti powder in nitrogen environment - Mridha, Shahjahan; Dyuti, S.; Shaha, S.K. (2011)
The formation of hard surface layer on steel provides a protective coating against wear, thermal loads and corrosion. In the present work a hard composite layer is formed on steel surfaces by preplacement of titanium powder and melted under nitrogen environment. Surface melting was conducted using TIG torch with different energy inputs. The microstructure and the morphology of the melt tracks were investigated using SEM and X-ray diffraction. The in-situ melting of titanium powder in nitrogen atmosphere produced dendritic microstructure of titanium nitride. The melt layer contained dispersed TiN, Ti2N dendrites highly populated at the surface compared to the deeper melt and gave a maximum surface hardness of around 1927 Hv. The wear property of the melt track was investigated using pin-on-disk tribometer at room temperature. The modified surface layer gave a low friction value of 0.12 and wear rate of 0.007895 ×10-4 compared to 1.648 × 10-4 mm3/N/m for the uncoated steel surface.